The filipino wordnet construction - Bondoc, Ron Jeremy (Philippine computing journal)
We present a serious preliminary undertaking and manual population of the Wordnet for the Filipino Language. Numerous Wordnets that cater to specific language exist today except for the Filipino Language. This became one of the main motivators to pursue this study, as well as, providing for a quality linguistic resource for a wide array of Natural Language Processing (NLP) tools dealing with the Filipino Language. The blueprint for the Filipino Wordnet was the original Wordnet created in Princeton University and also served as the basis for the database design. The manual creation of the synonym sets (synsets) was also facilitated from the English Wordnet. A tool was developed to assist the manual creation and editing of synset entries in order to decrease the tediousness and complexity of manual population. This tool is equipped with several NLP tools that are relevant to facilitating the manual creation of synsets. The tools include a morphological generator and analyzer, a concordancer, and a bilingual translator. Evaluations were done on the tools usability as well as the quality of the synsets created. Overall, the usability was very satisfactory while the quality of 200 synsets from more than 10,000 synsets with over 14,000 unique words created were high and only 9% had inaccuracies in definitions.